Scaling Stateful Network Services on Multicore Architectures - Carvalho, Fabrício B.; Ferreira, Ronaldo A. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2025)
This thesis investigates the effective scheduling of TCP stacks alongside applications on multicore architectures, focusing on the trade-offs in allocating workers for both TCP and application processing. It explores the interplay between stateful network protocols with strong guarantees and the challenges of scheduling such protocols alongside multicore applications. To allow fair comparisons, we design and implement Demieagle, a benchmark framework that allows the execution of “apples-to-apples” experiments to uncover the trade-offs of different multicore scheduling policies and architectures. We also address the complexity of scaling stateful network functions, which require per-packet state updates. During a scaling operation, workers need to synchronize access to a shared state to avoid race conditions and to guarantee that network functions process packets in arrival order. Unfortunately, the classic approach to control concurrent access to a shared state with locks does not scale to today’s throughput and latency requirements. To address these challenges, we design, implement, and evaluate Dyssect, a system that enables dynamic scaling of stateful network functions by disaggregating their states. Dyssect’s state disaggregation allows the offloading of stateful network functions to programmable NICs and makes it easier to explore hardware-software trade-offs that better suit specific network functions and traffic loads. Our experimental evaluation shows that Dyssect reduces tail latency up to 32.04% and increases throughput up to 19.36% compared to state-of-the-art competing solutions.